Gene-environment interactions in parkinsonism and Parkinson's disease: the Geoparkinson study. Issue 10 (20th April 2007) - Dick, F D; De Palma, G; Ahmadi, A; Osborne, A; Scott, N W; Prescott, G J; Bennett, J; Semple, S; Dick, S; Mozzoni, P; Haites, N; Wettinger, S Bezzina; et al.
Abstract : Objectives: To investigate associations of Parkinson's disease (PD) and parkinsonian syndromes with polymorphic genes that influence metabolism of either foreign chemical substances or dopamine and to seek evidence of gene-environment interaction effects that modify risk. Methods: A case-control study of 959 prevalent cases of parkinsonism (767 with PD) and 1989 controls across five European centres. Occupational hygienists estimated the average annual intensity of exposure to solvents, pesticides and metals, (iron, copper, manganese), blind to disease status. CYP2D6, PON1, GSTM1, GSTT1, GSTM3, GSTP1, NQO1, CYP1B1, MAO-A, MAO-B, SOD 2, EPHX, DAT1, DRD2 and NAT2 were genotyped. Results were analysed using multiple logistic regression adjusting for key confounders. Results: There was a modest but significant association between MAO-A polymorphism in males and disease risk (G vs T, OR 1.30, 95% CI 1.02 to 1.66, adjusted). The majority of gene-environment analyses did not show significant interaction effects. There were possible interaction effects between GSTM1 null genotype and solvent exposure (which were stronger when limited to PD cases only). Conclusions: Many small studies have reported associations between genetic polymorphisms and PD. Fewer have examined gene-environment interactions. This large study was sufficiently powered to examine these aspects. GSTM1 null subjects heavily exposed to solvents appear to be at increased risk of PD. There was insufficient evidence that the other gene-environment combinations investigated modified disease risk, suggesting they contribute little to the burden of PD.